2004
DOI: 10.1111/j.1601-5223.1998.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies of Powdery Mildew Resistance in Cultivated Oat (Avena Sativa L.) II. Cultivars and Breeding Lines Grown in Northern and Europe

Abstract: Cultivated oat (Avenu sativa L.) varieties and lines grown in Northern and Eastern European countries were tested for powdery mildew resistance using eleven Erysiphe graminis f. sp. avenue isolates, which possess the ability to differentiate the five oat powdery mildew resistance (OMR) groups. About 5%) from a total of 207 accessions possessed resistance which was attributable to either documented resistance or to disease response patterns previously not yet detected. Five cultivars and lines showed the resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 7 publications
0
48
0
2
Order By: Relevance
“…Several sources with major gene resistance to powdery mildew, including common oats (Jones 1983 ;Hsam et al 1997 ), wild oat species such as A. barbata (Aung et al 1977 ;Thomas et al 1980 ), A. strigosa , A. occidentalis (Herrmann and Roderick 1996 ), A. pilosa , and A. sterilis (Hayes and Jones 1966 ), have been reported. Two main sources of powdery mildew resistance are currently deployed in European oat breeding programs (Roderick et al 2000 ).…”
Section: Powdery Mildew Resistance Genesmentioning
confidence: 97%
See 1 more Smart Citation
“…Several sources with major gene resistance to powdery mildew, including common oats (Jones 1983 ;Hsam et al 1997 ), wild oat species such as A. barbata (Aung et al 1977 ;Thomas et al 1980 ), A. strigosa , A. occidentalis (Herrmann and Roderick 1996 ), A. pilosa , and A. sterilis (Hayes and Jones 1966 ), have been reported. Two main sources of powdery mildew resistance are currently deployed in European oat breeding programs (Roderick et al 2000 ).…”
Section: Powdery Mildew Resistance Genesmentioning
confidence: 97%
“…Clifford ( 1995 ) reported annual crop losses from 5 to 10 % in Great Britain, with much higher reductions in small plot trials. Hsam et al ( 1997 ) investigated powdery-mildew resistance in 259 common oat cultivars and breeding lines. They found 67 % of the investigated plants were susceptible to this disease.…”
mentioning
confidence: 99%
“…The results obtained in our study suggest that selected genotypes could be used as donors of genes encoding Plant Pathol (2014) 139:9-12resistance to powdery mildew. Moreover, Hsam et al (1997Hsam et al ( , 1998; Kowalczyk et al (2004) and Okoń (2012) in their study identified some resistant oat cultivars possessed an unknown response pattern compared to control cultivars. These resistant genotypes could be also used as new sources of resistance in oat breeding programs.…”
mentioning
confidence: 95%
“…Many sources of resistance to powdery mildew have been reported in common oat (Jones 1983;Hsam et al 1997Hsam et al , 1998 as well as in wild relatives of A. sativa (Aung et al 1977;Thomas et al 1980;Herrmann and Roderick 1996;Hoppe and Kummer 1991;Hayes and Jones 1966). The study of Sebesta et al (1991) indicated that the line Pc54, which originated from a hybrid between A.sativa cv Pendek and A.sterilis, possessed effective resistance to powdery mildew.…”
mentioning
confidence: 99%
See 1 more Smart Citation